Optimization of Arabic Scientific Writing Based on the Growth Mindset of IUQI Bogor and STITMA Yogyakarta Students - Fatchiatuzahro; Milahtul Latifah; Agung Maulana Mansyur (al-Afkar, Journal For Islamic Studies, 2024)
Optimizing writing scientific papers in Arabic based on a growth mindset is very urgent to help students' difficulties in writing scientific papers in Arabic, both in terms of knowledge and mental aspects, because scientific work is a requirement for graduating from undergraduate education taken by PBA IUQI Bogor and STITMA Yogyakarta study program students. This research uses the service-learning method in four stages: investigation, preparation, implementation, and reflection. Based on 22 respondents choosing answers of strongly agree and agree regarding the success of implementing assistance in writing scientific papers in Arabic, as detailed in the diagram, responses of disagree and strongly disagree were not found from the participants' responses. Thus, it was concluded that implementing assistance in writing scientific papers in Arabic was successful and beneficial for the participants.